Efektivitas Layanan Informasi dengan Pendekatan Contextual Teaching And Learning dalam Meningkatkan Arah Perencanaan Karier Siswa SMK - Putri, Ramtia Darma; S, Neviyarni; Irianto, Agus (Universitas Negeri Padang, 2015)
Direction of career planning become very important because it can guidelines students in decisions making of his career in the future.Â Direction of career planning should be prepared and improved considering that not all students have a mature direction of career planning. Central Statistics Agency (BPS) of West Sumatera in August 2014 recorded the open unemployment of about 6.99%Â or reach 150 thousand people are more dominated by graduates SMK as much as 11.15%. In addition, the results of AUM umum in one of the SMK was indicated problems in careers and jobs as much to 33.56%. This demonstrates that students do not have a clear understanding about direction of career planning that will be chosen. One of the efforts to improve the students direction of career planning is the information service.Â This research was intended to find out the effectiveness of information service with contextual teaching and learning approach to improve the direction of career planning student of SMK.This study uses quantitative methods. This type of research is Quasi Experiment with Nonrandomized Control Group Pretest-posttest Design. The subjects were students of SMK Padang Nusatama as an experimental group and the SMK Nasional Padang as a control group. The research instrument used Likert Scale models, and then analyzed using Paired Samples t-test and Independent Sample t-test with SPSS version 17.00.In general the study's findings that information service with contextual teaching and learning approach is effective in improving direction of career planning student of SMK. Specifically: (1) there was a significant differences between direction of career planning in the experimental group before and after the given information service with contextual teaching and learning approach, (2) there was a significant differences between direction of career planning in the control group before and after the given conventional information service, and (3) there was a significant differences between direction of career planning in the experimental group who were information service with contextual teaching and learning approach and those in the control group who were conventional information service.